Agricultural supply response and poverty in Mozambique - Heltberg, R.; Tarp, F. (Food Policy, 2002)
This paper identifies key causal factors behind farmers’ marketing decisions in Mozambique. A two-step decision making process is outlined. Farmers decide, first, whether or not to participate in the market. Next, they decide how much to sell. The model is estimated using a Heckman switching regression approach. The key importance of non-price factors such as risk, technology and transport infrastructure come out clearly. Marginal effects are calculated for poor and nonpoor households and broken down into a market participation and a quantity (sales value) component. The marginal effects for the poor are not substantially different from those of the nonpoor. This suggests that differences in area-based characteristics (especially risk and technology) are more influential in the commercialization process than differences in how the poor and the nonpoor respond to incentives. Moreover, interventions to promote market access are likely to solicit a greater volume of additional supply from peasants entering the market for the first time than from existing market participants stepping up their production and sales. To achieve pro-poor rural growth it is essential to address explicitly the conditions of high-risk, low productivity and low capital endowments of poor farmers.
Keywords: G - Mozambique / Moçambique; L - english / inglês